Oblicz:
( √64) ² * [½)]³ + √0,49 ² : 76 *75
________
103 * 0,1 ²



przekształc wyrażenie a następnie oblicz dla x=4
[ x do potęgi 6 : ( x do potęgi 5 : x do potęgi 3) ] : [x do potęgi 7 * x do potęgi 2= x do 6 : x do 2 '] do 4 : [x do 2 * x do 6 ' = (x) : x do 13

obliczniaa pliss bd naj

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-12T19:16:00+01:00
Oblicz:
( √64) ² * [½)]³ + √0,49 ² : 76 *75
________
103 * 0,1 ²

= (2⁶)² do pot 1/2 * (2⁻¹)³ + √49/100²:76*75
_______
103*1/100

= 2⁶*2⁻³+49/100:5700
___________
103/100

= 2³+49/570000
_________
103/100

= 8 i 49/570000
________
103/100

= 8 i 49/570000 * 100/103 = 443,19


przekształc wyrażenie a następnie oblicz dla x=4
[ x do potęgi 6 : ( x do potęgi 5 : x do potęgi 3) ] : [x do potęgi 7 * x do potęgi 2= x do 6 : x do 2 '] do 4 : [x do 2 * x do 6 ' = (x) : x do 13

[x⁶:x²]:[x⁹]=x⁴:x⁹=x⁻⁵=4⁻⁵= 1/1024
(x⁴)⁴:x⁸=x¹⁶:x⁸=x⁸= 65536
x⁻¹²=1/16777216